2009
DOI: 10.1039/b816701j
|View full text |Cite
|
Sign up to set email alerts
|

Domino reactions of rhodium(ii) carbenoids for alkaloid synthesis

Abstract: In this tutorial review, the rhodium(II)-catalyzed domino reactions of alpha-diazo carbonyl compounds are summarized. The article will emphasize some of the more recent synthetic applications of the rhodium carbenoid cyclization/cycloaddition domino cascade for alkaloid synthesis. The many structurally diverse and highly successful examples of both oxa and azapolycyclic ring formation cited in this tutorial review clearly demonstrate that the domino cyclization/cycloaddition cascade of metallo carbenoids has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(112 citation statements)
references
References 56 publications
2
108
0
2
Order By: Relevance
“…Table 3 summarizes experiments carried out to probe the scope of the present transformation. Investigation of the effect of the substituent on the Ar group showed that comparable enantioselectivities were observed irrespective of the electronic character and position of the substituent introduced on the phenyl ring (Table 3, entries [1][2][3][4][5]. The a-diazocarbonyl compounds 3 having substituents on the basal aromatic ring also underwent the consecutive transformation to afford isochromene derivatives 6 in good yields (Table 3, entries 6 and 7).…”
Section: Masahiro Terada* and Yasunori Todamentioning
confidence: 90%
“…Table 3 summarizes experiments carried out to probe the scope of the present transformation. Investigation of the effect of the substituent on the Ar group showed that comparable enantioselectivities were observed irrespective of the electronic character and position of the substituent introduced on the phenyl ring (Table 3, entries [1][2][3][4][5]. The a-diazocarbonyl compounds 3 having substituents on the basal aromatic ring also underwent the consecutive transformation to afford isochromene derivatives 6 in good yields (Table 3, entries 6 and 7).…”
Section: Masahiro Terada* and Yasunori Todamentioning
confidence: 90%
“…42, Scheme 8.8) 25 or cycloadditions (e.g., 43 ! 44, Scheme 8.8) 26 depending on the type of ylide formed (Scheme 8.8). In the case of silver-derived carbenes, this area has only recently begun to attract attention, and therefore there are only limited examples reported in the literature.…”
Section: Formation and Reactions Of Ylidesmentioning
confidence: 99%
“…NMR spectra were recorded on a Jeol-400 NMR spectrometer. 1 H-NMR (400 MHz), and 13 C-NMR (100 MHz) were run in either deuterated chloroform (CDCl 3 ) or deuterated dimethylsulphoxide (DMSO-d 6 ). Chemical shifts (δ) are referred in terms of ppm and J -coupling constants are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Multicomponent reactions (MCRs) are one of the most powerful research protocol for generation of complex polyfunctionalized molecules using convergent one-pot transformations [1][2][3][4][5][6][7]. In addition, multicomponent reactions in green solvent such as water are of considerable interest.…”
Section: Introductionmentioning
confidence: 99%